Pengembangan Sistem Informasi Sumber Daya Manusia pada PT. Toyogiri Iron Steel berbasis Web - Mas Haq Kresno Danisworo Astroaji C; Denny Sagita Rusdianto; Eriq Muhammad Adams Jonemaro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
There are problems in the HR department at PT.Toyogiri Iron Steel. The first problem is the procedure for applying for overtime, leave and permission. Employees who make submissions must ask for signatures from their superiors and department heads before being approved by HRD. This creates a problem, the boss is not in the factory or not present. HRD also cannot monitor employee overtime. HRD checks employees who are doing overtime whether it is in accordance with the proposed hours. Not yet integrated between salary calculation and attendance. The integration of components such as attendance data recapitulation, overtime, permits, leave, allowances and deductions in salary. The HRD entered manually where time was less efficient. And provides additional functions such as issuing warning letters, suspension and promotion / demotion. From these problems, the authors will create a web-based human resource information system at PT. Toyogiri Iron Steel. This system functions to store information, assist applications for overtime, leave and permits, integration of attendance and payroll, submit promotion / demotion and warnings. Development of a web-based system developed with the waterfall style SDLC. The system is created with object-oriented design and uses the MVC (Model-View-Controller) method in the CodeIgniter framework by dividing it into 3 parts, a model for interaction to the database, a controller for the main logic, and a view for the system view, and MySQL and MariaDB as the database. From the results of requirements engineering, there are 64 functional requirements and 1 non-functional requirement. In the design and implementation results, the PHP programming language is used with the CodeIgniter framework. The interface implementation uses the HTML, CSS, and Javascript programming languages. In system testing, unit testing is carried out using white box testing with the basis path testing method tested on 3 sample functions with all valid values. Validation testing is tested for all functional requirements with all valid values. Validation testing for compatibility, system applications were tested on 6 different web browsers with all the results running well.